A nasal double DNA adjuvant system induces atheroprotective IgM antibodies via dendritic cell-B-1a B cell interactions. Issue 8 (16th February 2022) - Yoshimatsu, Hideki; Kataoka, Kosuke; Fujihashi, Kohtaro; Miyake, Tatsuro; Ono, Yoshiaki
Graphical abstract: Highlights: Nasal PC plus double DNA adjuvant vaccination induces mucosal and systemic T15 idiotype-like Abs. Nasal PC with double DNA adjuvant increases the frequencies of DCs and B-1a B cells. Nasal PC plus double DNA adjuvant vaccination decreases plaque accumulation in the aorta. Nasal double DNA adjuvant system enhances expression of APRIL/BAFF on DCs and TACI on B-1a B cells. Abstract: We previously demonstrated that the dendritic cell (DC)-targeting nasal double DNA adjuvant system, which consists of a DNA plasmid expressing Flt3 ligand (pFL) and CpG oligodeoxynucleotide 1826 (CpG ODN), elicits specific immune responses to various antigens in the mucosal and systemic compartments. Here, we investigated, using phosphorylcholine (PC)-conjugated keyhole limpet hemocyanin (PC-KLH) as an antigen, whether the nasal double DNA adjuvant system induces protective immunity to atherosclerosis in apolipoprotein E-deficient ( ApoE KO) mice. Further, we assessed the molecular and cellular mechanisms in the induction of anti-PC-specific immune responses . Nasal immunization with PC-KLH plus pFL and CpG ODN enhanced induction of PC-specific IgM in plasma, peritoneal fluids, and nasal washes when compared with mice administered PC-KLH alone. Of importance, these antibodies exhibited highly specific binding to the PC molecule, and dose-dependent binding to anti-T15 idiotype (AB1-2). Twelve weeks after the last immunization, the nasal double DNA adjuvant system with PC-KLH resulted in a reduction of atherogenesis in the aortic arch of ApoE KO mice. Therefore, we next assessed immunocytological mechanism to induce these antibodies. The nasal double DNA adjuvant system with PC-KLH resulted not only in significantly increased frequencies of CD11c + DCs in the spleen, peritoneal cavity (PEC), and nasopharyngeal-associated lymphoid tissues (NALT), but also significantly increased expression of a proliferation-inducing ligand and B-cell-activating factor by CD11c + DCs. In addition, the double DNA adjuvant system induced significantly increased numbers of B-1 B cells in the spleen, PEC, and NALT, and increased expression of transmembrane activator and calcium modulator and cyclophilin ligand interactor on CD5 + B220 + (B-1a) B cells. These findings demonstrated that the nasal double DNA adjuvant system with PC-KLH resulted in the induction of T15-like antibodies in the mucosal and systemic lymphoid tissues through interaction between DCs and B-1a B cells, and inhibited the progression of atherogenesis.